Acer japonicum - Edward F. Gilman (EDIS)
Full-moon maple is a small, deciduous tree that reaches 10 to 15 feet in both height and width, creating a smooth, rounded canopy (Figure 1). It fits well into the oriental garden due to its exotic silhouette. The cultivar 'Acontifolium' is exceptionally cold hardy, having survived temperatures of 25°F below zero. The deeply divided, soft green leaves have 9 to 11 lobes and are delicately displayed on thin, drooping branches. The cultivar 'Vitifolium's' leaves are less divided, providing a coarse texture in the landscape. Leaves take on a beautiful yellow to red coloration in the fall before dropping, making this small, dense plant really stand out in the landscape. Fall color has been described as exceptional. The hanging clusters of showy, purple/red flowers appear in late spring and are followed by the production of winged seeds. The full-moon maple's flowers stand out among the maples. This document is FPS 007, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 1, 1999. Revised October 1, 2004. Reviewed October, 2004.